Effect of distinct impact loading sports on body composition in pre-menarcheal girls - Milanese, C.; Piscitelli, F.; Cavedon, V.; Zancanaro, C. (Science & Sports, 2014)
Introduction: The aim of this preliminary work was to explore the effect of distinct impact loading sport and different amount (h/w) of impact activity on body composition of pre-menarcheal girls. Subjects and methods: This study included 30 pre-menarcheal girls (aged 8.0-12.9 years) training for at least 1 year in volleyball (VOLLEY, n = 10) or artistic gymnastics at high (HGYM, n = 10) and low (LGYM, n = 10) amount (h/w) of training. Body composition (bone mineral content [BMC], fat-free soft tissue mass [FFST], fat mass [FM], and %FM) was assessed by dual-energy X-ray absorptiometry (DXA) at the total body (TB) and regional (arms, legs, trunk) level as well as specific axial skeleton sites (thoracic and lumbar spine, pelvis). Results: After adjusting for body mass and stature, TB composition measurements were all significantly (P < 0.01) different in the three groups of pre-menarcheal athletes. VOLLEY had lower BMC and FFST, and greater FM and %FM vs. both HGYM and LGYM. The main difference between LGYM and HGYM was greater %FM in the former. Similar results were found at the regional level (but for similar BMC in the legs) and at lumbar spine and pelvis. Conclusion: This study suggests that in pre-menarcheal girls training in impact loading activity, difference in sport type mainly affect %FM, and the amount of impact activity (h/w) has major impact on BMC accrual.